The Effect of the Educational Program on Knowledge and Care Behaviors of Children with Thalassemia in Phrae hospital - Somjit, Chunjit; Attachaipanich , Kanokrat; Suma , Anyarat (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
This quasi- experimental research aimed to compare average knowledge and self care behaviors score of school age children with Thalassemia before and after attend the educational program. Design the study by two group pretest-posttest exam in 7-12 years old transfusion dependent Thalassemia children that attended Phrae hospital during August–November, 2021. Experimental group was 19 transfusion dependent Thalassemia children that attended hospital on Tuesday receiving the educational program on knowledge and self care behaviors through animation and comic. Control group was 19 blood dependent Thalassemia children that attended hospital on Monday receiving routine care. Basic data were collected using exact probability test and t-test. Average knowledge and care behaviors score were compared by t-test and paired t-test.